The Effect of Experimental Methods on Visuals Activities and Skills Think Critical on Learning IPAS Change of Form Material - Neviasari, Wendi; Anggoro, Subuh (Proceedings Series on Social Sciences & Humanities, 2025)
Study This aiming For researching influence method experiment to visual activities and critical thinking skills in science learning for grade IV at SD Negeri Kebonmanis 01. The research method used is the quasi-experimental method of sample selection in the Quasi Experimental type Nonequivalent Control Group Design. The research sample consisted of 59 fourth grade students who were divided into two groups, namely the experimental group and the control group. The experimental group was given learning treatment. IPAS with use method experiment, whereas group control was given the treatment of science learning using conventional methods. Research data were collected through observation, visual activities tests , and critical thinking tests. The results of the study showed that there was a significant influence on visual activities and critical thinking skills of fourth grade students taught using experimental methods compared to students taught using conventional methods. This shows that the experimental method is effective in improving visual activities and critical thinking skills of fourth grade students in science learning.